Pengaruh Pandemi Covid-19 Terhadap Minat Penggunaan Layanan Mobile Banking: Studi kasus pada PT Bank Central Asia Tbk Kantor Cabang Utama Bogor - Sudjali, Iwan Purwanto; Akbar, Muhammad Alwi; Rosa, Edy Safni (Jurnal Informatika Kesatuan, 2023)
Currently, Indonesia is experiencing a national disaster in the form of the Covid-19 which is a virus with a very fast transmission rate.pandemic Covid-19 is allegedly not only attacking health but also affecting the global economy. In the end, many people use digital transactions such as Mobile banking during this pandemic. Mobile Bankingaservice provided by banks to facilitate their customers in transacting anywhere and anytime. Mobile banking useful for customers in carrying out government policies of stay at home and physical distancing to break the chain of virus spread during the covid 19 This study aims to determine the effect of Stay at home (X1) and Physical distancing (X2) on interest in using Mobile banking (Y) during the Covid-19. The method used in this study is multiple linear regression analysis, this is an analysis that describes the form of influence between one or more variables with other variables. The type of data used in this study is a secondary data source that was processed from 100 respondents from customers of Bank Central Asia Tbk Bogor Main Branch Office. Based on the results of data processing, there is a significant positive effect between stay at home on interest in using Mobile banking services at PT Bank Central Asia Tbk Bogor Main Office, there is a significant positive effect between physical distancing on interest in using Mobile banking services at PT Bank Central Asia Tbk Bogor main office. There is a joint influence of stay at home and physical distancing on the Interest in Using Mobile banking Services PT Bank Central Asia Tbk Bogor Main Office. Keywords: Stay at home, physical distancing, intention, and Mobile Banking